THE EFFECTS OF ANIMAL-ASSISTED ACTIVITIES (AAA) ON THE WELL-BEING OF MINORITY STUDENTS IN GERMANY - Sokal, Laura; Kahl, Anna (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2019)
Global increases in mental illness in children and youth have precipitated a wide range of therapies to address this concern. An alternative to this reactive approach is based on models of mental wellness that enhance children’s and youths’ perceptions of well-being and health. The current project examined the effects of a universal animal-assisted activity (AAA) program on a group of minority students who attended a boarding school in Germany. The intent of the current study was to determine whether the duration and types of AAA the students experienced were associated with higher levels of perceived mental well-being. Short-term gains in calmness were demonstrated under some AAA conditions, and long-term gains in well-being resulted from minority children’s participation in rabbit club.